2023
DOI: 10.5194/egusphere-egu23-1871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seaweed as a resilient food solution in nuclear winter

Abstract: <p>Abrupt sunlight reduction scenarios such as a nuclear winter, an asteroid impact or an eruption of a supervolcano would decimate agriculture as it is practised today. We therefore need resilient food sources for such an event. One promising candidate is seaweed, as it can grow quickly in a wide range of environmental conditions. To explore the feasibility of seaweed in a nuclear winter, we simulate the growth of seaweed on a global scale using an empirical model based on <em>Grac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…By incorporating more precise and comprehensive datasets into this analysis, its accuracy could be improved. Exploring resilient food options that could serve as viable alternatives to conventional food production in the event of global catastrophic infrastructure loss. For instance, seaweed, which has demonstrated promise following other global catastrophes, [ 47 ] may also prove beneficial in this context due to its ability to thrive in low‐tech cultivation. Also, leaf protein concentrate can be produced at the community scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating more precise and comprehensive datasets into this analysis, its accuracy could be improved. Exploring resilient food options that could serve as viable alternatives to conventional food production in the event of global catastrophic infrastructure loss. For instance, seaweed, which has demonstrated promise following other global catastrophes, [ 47 ] may also prove beneficial in this context due to its ability to thrive in low‐tech cultivation. Also, leaf protein concentrate can be produced at the community scale.…”
Section: Discussionmentioning
confidence: 99%
“…For sun-blocking scenarios like a supervolcanic eruption this includes the exploration and preparation of resilient foods such as single-cell protein from natural gas, [43] hydrogen, [44] sugar from wood, [45] greenhouses, [46] or seaweed. [47] More traditional resilience measures include food storage, diversification of agricultural practices, crop insurance, or regulations of the agricultural market. [1,15] Most of these solutions, however, depend on industrial infrastructure in one way or another or assume that only a smaller subsection of global food production is impacted.…”
Section: Introductionmentioning
confidence: 99%
“…• Nuclear winter ocean data: Jehn et al (2023b). helped with the initial scoping of the project by running some of the ocean model data through his growth model and providing said growth model to the project, but passed away in 2021.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…For a detailed description of the factors see Figures S10-S14 in Supporting Information S1. The code (Jehn et al, 2023a) and data (Jehn et al, 2023b) for the growth model can be found at the corresponding repositories. We excluded the self-shading factor in our adaptation of the growth model and only looked at it in the scale-up model, as it is more relevant for continuous harvesting and less so for assessing if seaweed can grow after nuclear war at all.…”
Section: Seaweed Growth Modelmentioning
confidence: 99%
See 1 more Smart Citation